Properties of sustainable concrete with substitution of recycled coarse aggregate - D. Fatimah Zahara Natasyaida Idris Alli (School of Environmental Engineering, University Malaysia Perlis, 2013)
This research was carried out to produce a new concrete by using recycle aggregates obtained from construction and demolition.